(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper aims to explore when therapist disclosure is ’acceptable’, the difference between in-therapy and in-the-(non-therapy-)world. The discussion from the 2017 conference is briefly reflected upon, along with examples since of disclosure being present in-therapy in an unpredictable way. The idea of needing to think through how (unknown) clients may feel is discussed with a view that therapists are deserving of the life they want, and in that sense, should be permitted to engage with the world as they find it, how they want to. Freud, or rather Reich, argued the therapist needs to be a blank screen, something for the client to use to project onto them whatever needs exploring (Reich, 1933). Contrarily, I would argue that as a psychotherapist in the modern day, we should be true to our own opinions, certainly outside the therapy room, ideally inside as well (depending on the situation) and be involved in the world however we want to be rather than conforming, or even trying to conform, to an archaic stereotyping of our profession.